2013
DOI: 10.1371/journal.pone.0056146
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Fungal β-Mannanase from Bispora sp. MEY-1 in Maize Seeds and Enzyme Characterization

Abstract: BackgroundMannans and heteromannans are widespread in plants cell walls and are well-known as anti-nutritional factors in animal feed. To remove these factors, it is common practice to incorporate endo-β-mannanase into feed for efficient nutrition absorption. The objective of this study was to overexpress a β-mannanase gene directly in maize, the main ingredient of animal feed, to simplify the process of feed production.Methodology/Principal FindingsThe man5A gene encoding an excellent β-mannanase from acidoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The value of such low-phytate maize products has been recently confirmed in feeding trials with poultry (Gao et al, 2012;Ma et al, 2013;Wang et al, 2013e) and pigs (Li et al, 2013d). A similar benefit may derive from GM maize expressing a fungal β-mannanase from Bispora (Xu et al, 2013b).…”
Section: Enzymes Diagnostics and Vaccinesmentioning
confidence: 84%
“…The value of such low-phytate maize products has been recently confirmed in feeding trials with poultry (Gao et al, 2012;Ma et al, 2013;Wang et al, 2013e) and pigs (Li et al, 2013d). A similar benefit may derive from GM maize expressing a fungal β-mannanase from Bispora (Xu et al, 2013b).…”
Section: Enzymes Diagnostics and Vaccinesmentioning
confidence: 84%
“…The preparation of polyclonal antibody of Aga-F75 in rabbits (6 pounds and greater) was conducted in the Laboratory of Animal Center, Institute of Genetics and Developmental Biology, Chinese Academy of Sciences (Beijing, China) following the rules and protocols approved by the Experimental Animal Ethics Committee of Chinese Academy of Sciences. The purification of polyclonal antibody and the procedures of Western blot were carried out as described previously [ 17 ]. The bands were then excised from the gel for protein identification by matrix assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry at Tianjin Biochip Corporation (Tianjin, China).…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli and Pichia pastoris ) [ 8 , 16 ] has some disadvantages like high equipment cost, high energy consumption, serious environment pollution, complex processing, etc. An efficient and economic alternative is to produce α-galactosidase directly in feed grains as β-mannanase and xylanase produced in transgenic maize [ 17 ] and rice [ 18 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…MEY-1 β-mannanase under the control of an embryo-specific promoter were tested because Bispora is an acidophile and the enzyme should therefore remain functional in the low-pH gastric environment. The enzyme was found to remain active under the same conditions as the commercial supplement from P. pastoris but was more thermotolerant during pelleting, with an activity of 10,000 U/kg (87). A feeding trial of β-mannanase supplements in pigs revealed that 400 U/kg feed achieved the greatest feed efficiency, so 40 g of the transgenic seeds per kilogram of conventional diet is sufficient to achieve the anticipated effects (88).…”
Section: Products Without the Need For Purification Feed Additivesmentioning
confidence: 96%
“…The enzyme was also resistant to gastric digestion allowing it to act on phytate in the gut. Following successful field trials in chickens, phytaseenhanced maize was released as China's first transgenic crop in 2009, and the biosafety certificate was renewed in 2015 (87).…”
Section: Products Without the Need For Purification Feed Additivesmentioning
confidence: 99%